The Recent Development of Multifunctional Gold Nanoclusters in Tumor Theranostic and Combination Therapy - Sisi Liu; Junyao Wang; Yuxin Song; Shuya He; Huaxin Tan (Pharmaceutics, 2022)
The rising incidence and severity of malignant tumors threaten human life and health, and the current lagged diagnosis and single treatment in clinical practice are inadequate for tumor management. Gold nanoclusters (AuNCs) are nanomaterials with small dimensions (≤3 nm) and few atoms exhibiting unique optoelectronic and physicochemical characteristics, such as fluorescence, photothermal effects, radiosensitization, and biocompatibility. Here, the three primary functions that AuNCs play in practical applications, imaging agents, drug transporters, and therapeutic nanosystems, are characterized. Additionally, the promise and remaining limitations of AuNCs for tumor theranostic and combination therapy are discussed. Finally, it is anticipated that the information presented herein will serve as a supply for researchers in this area, leading to new discoveries and ultimately a more widespread use of AuNCs in pharmaceuticals.